2020
DOI: 10.1002/jobm.202000515
|View full text |Cite
|
Sign up to set email alerts
|

UV‐B tolerances of conidia, blastospores, and microsclerotia of Metarhizium spp. entomopathogenic fungi

Abstract: The aim of the present study was to analyze ten native Metarhizium spp. isolates as to their UV‐B tolerances. Comparisons included: different fungal propagules (conidia, blastospores, or microsclerotia [MS]); conidia in aqueous suspensions or in 10% mineral oil‐in‐water emulsions; and conidia mixed with different types of soil. The UV‐B effect was expressed as the germination of conidia or culturability of blastospores and MS relative to nongerminated propagules. Metarhizium anisopliae LCM S05 exhibited high t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 60 publications
1
12
0
2
Order By: Relevance
“…Here, the culturability of Metarhizium conidia and microsclerotia was less impacted than that of blastospores, when used in combination with the acaricides (Figure 1). Conidia are produced by phialides (in a process called conidiogenesis), while microsclerotia are clusters of melanized hyphae that are highly resistant to oxidative stress and capable of producing microbial compounds, and blastospores are vegetative structures produced by hyphal budding that gives them a weaker membrane (Hallsworth & Magan, 1996;Song et al, 2016;Kim et al, 2013;Jackson & Payne, 2016;Bernardo et al, 2020;Corval et al, 2021). It is suggested that differences in the physical structures of propagules can impact their susceptibility to synthetic acaricides and this assumption is supported by our results.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Here, the culturability of Metarhizium conidia and microsclerotia was less impacted than that of blastospores, when used in combination with the acaricides (Figure 1). Conidia are produced by phialides (in a process called conidiogenesis), while microsclerotia are clusters of melanized hyphae that are highly resistant to oxidative stress and capable of producing microbial compounds, and blastospores are vegetative structures produced by hyphal budding that gives them a weaker membrane (Hallsworth & Magan, 1996;Song et al, 2016;Kim et al, 2013;Jackson & Payne, 2016;Bernardo et al, 2020;Corval et al, 2021). It is suggested that differences in the physical structures of propagules can impact their susceptibility to synthetic acaricides and this assumption is supported by our results.…”
Section: Discussionsupporting
confidence: 78%
“…Three milliliters of conidial suspensions (10 8 conidia ml -1 ) were inoculated into 50 ml of oatmeal broth (60 g of oat flour and 42.1 gl -1 of glucose) at 200 rpm for 72 h at 25 °C ± 1 °C. The blastospores were produced as described by Corval et al (2021). The suspensions were adjusted to 2.0 × 10 3 blastospores ml -1 .…”
Section: Compatibility Of Metarhizium Spp Blastospores With Commercia...mentioning
confidence: 99%
“…In comparison with the non-formulated conidia, oil emulsion formulation prolongs the shelf life and improves the pathogenicity of entomopathogenic fungi against the insect pests, such as the citrus psyllids [ 10 ] and mealybugs [ 11 ]. Various oil carriers, namely mineral and sunflower oil, have been used to prepare oil-based formulations [ 12 , 13 ]. Additionally, sesame oil was also found to prolong the food shelf life owing to the high content of polyunsaturated fats [ 14 ], suggesting the potential of oils as an effective carrier for the formulation of bioinsecticides.…”
Section: Introductionmentioning
confidence: 99%
“…Tanto los conidios como los blastosporos de M. robertsii IP 146 fueron igualmente tolerantes a la radiación UV-B (irradiancia 743,7 mW m -2 ); sin embargo, la viabilidad relativa fue menor que en los conidios aéreos cuando se exponen a 45 °C (Bernardo et al 2020). Recientemente, se reportó que la viabilidad de microesclerocios expuestos a la radiación UV-B (4.0 kJ m -2 ) varió mucho entre aislamientos de Metarhizium spp., algunos aislamientos fueron susceptibles y otros bastante tolerantes (Corval et al 2021). En este trabajo de tesis, se muestra por primera vez la tolerancia comparativa entre microesclerocios y pellets de M. robertsii ARSEF 2575 a la radiación UV-B (1.283,38 mW m -2 ).…”
Section: Discussionunclassified
“…La tolerancia a los rayos UV-B han sido reportados en propágulos como conidios, micelio o blastosporos de hongos entomopatógenos (Fernandes et al 2007(Fernandes et al , 2015Braga et al 2015;Rangel et al 2015;Brancini et al 2018;Zhao et al 2019;Bernardo et al 2020;Corval et al, 2021). La temperatura es un factor limitante durante la morfogénesis, la germinación y los procesos metabólicos (Abrashev et al 2008;Zhang et al 2017).…”
Section: Factores Abióticos En El Control Microbianounclassified